The Effect Of Product Innovation And Location On The Decision To Buy Sponge Cake At The Fitri Sari Shop In Arga Jaya Village - Mardhiyah Dwi Ilhami; Taufik Bustami; Satria Indra Permana (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the influence of product innovation and location on the decision to purchase sponge bread at the fitri sari store in Arga Jaya village. This study used quantitative methods and data collection by observation and questionnaire distribution. The samples in this study were consumers at the Arga Jaya village sari fitri store which amounted to 120 people and sampling was carried out using the Hair et al method. Based on the results of research and discussion of product innovation, it has a positive and significant effect on the decision to purchase sponge bread at the fitri sari store in Arga Jaya village, meaning that with the product innovation provided by the fitri sari store, of course, this will increase the level of purchase decisions. Location also has a positive and significant effect, meaning that with a location that is strategic enough and easy to access, consumers will increase in decision making. This equation can be explained by the positive influence of each independent variable, namely product innovation (X1) and location (X2) on the dependent variable, namely purchase decision (Y).